Small cell lung carcinoma: case study - Bravo, Ritha V.; Salazar, Sirced; Carballosa, Elizabeth; Cornejo, Anthony V.; Palma, Andrés S.; Cedeño, Kendry E. (Revista Gregoriana de Ciencias de la Salud, 2025)
Small cell lung carcinoma is a malignant neuroendocrine neoplasm characterized by rapid progression and high metastatic potential. This article presents the case of a 31-year-old male patient with no history of smoking who experienced persistent hemoptysis for one year, accompanied by asthenia and odynophagia. Imaging studies revealed a pulmonary mass located in the upper lobe of the left lung, involving the left main bronchus and accompanied by satellite nodular lesions, some of them cavitated. A CT-guided biopsy showed small, round-shaped cells with hyperchromatic nuclei and high mitotic activity. Immunohistochemical analysis revealed positivity for cytokeratin, TTF-1, CD56, and a moderate Ki-67 proliferation index, confirming the diagnosis of small cell lung carcinoma. This case is atypical due to the patient’s young age, the peripheral location of the tumor, and the absence of classical risk factors such as smoking.